A review of the geodynamic constraints on the development and evolution of geothermal systems in the Central Andean Volcanic Zone (18–28°Lat.S). Issue 10 (2nd July 2020) - Veloso, Eugenio E.; Tardani, Daniele; Elizalde, Daniel; Godoy, Benigno E.; Sánchez-Alfaro, Pablo A.; Aron, Felipe; Reich, Martin; Morata, Diego
ABSTRACT: Geothermal exploration in the Central Andean Volcanic Zone (CAVZ) focuses on heat capacities of known geothermal systems, yet the role of faults, veins, fractures and folds on the evolution and migration of fluids is far from complete. Here, we present a compilation of He and Sr isotope data and newly generated structural maps to examine if particular tectonic configurations are associated with fluids migrating from different crustal levels. Accordingly, we defined three tectono-geothermal environments (T1–T3) depicting specific structural arrangements and spatial relation with geothermal and volcanic manifestations. T1 is dominated by left-lateral strike-slip NW-striking faults, and geothermal and volcanic manifestations occur along the traces of these structures. T2 is dominated by N-striking thrust faults and parallel fault-propagated folds, cut and displaced by NW-striking faults. Here, geothermal manifestations occur at fault intersections and at fold hinges. T3 is defined by left-lateral/normal NW-striking faults, with geothermal and volcanic manifestations lying along fault traces. Each tectono-geothermal environment yields distinctive isotope ratios and geothermal reservoir temperatures. T1 shows high helium and low strontium ratios, and temperatures between 220° and 310°C. T3 shows low helium and high strontium ratios and temperatures between 260° and 320°C. T2 isotope ratios fall between T1 and T3, with lowest (130°-250°C) reservoir temperatures. We argue that these particular isotope signatures are due to a structural control on reservoir location and orientation. The orientation of the fracture mesh genetically associated with each tectono-geothermal environment is a first-order control on the migration pathway of fluids. Our model shows that T1 allows fluxing of deeper fluids, T2 promotes storage and favors longer residence times and T3 enhances subvertical fluid migration. Results here help to explain the evolution of geothermal systems in a wider context, including fault systems and Sr and He isotope variations, thus providing a framework for geothermal exploration in the CAVZ.